SbWRKY75- and SbWRKY41-mediated jasmonic acid signaling regulates baicalin biosynthesis - Fang, Shiyuan; Zhang, Chen; Qiu, Shi; Xiao, Ying; Chen, Kaixian; Lv, Zongyou; Chen, Wansheng (Frontiers in Plant Science, 2023)
Scutellaria baicalensis Georgi is a traditional Chinese medicinal plant with broad pharmacological activities whose main active ingredient is the flavonoid baicalin. Given its medicinal value and increasing market demand, it is essential to improve the plant’s baicalin content. Flavonoid biosynthesis is regulated by several phytohormones, primarily jasmonic acid (JA). In this study, we used transcriptome deep sequencing to explore the transcriptome of S. baicalensis roots treated with methyl jasmonate for different durations (1, 3, or 7 h). By combining weighted gene co-expression network analysis with transcriptome data, we identified candidate transcription factor genes that regulate baicalin biosynthesis. Yeast one-hybrid, electrophoretic mobility shift, and dual-luciferase assays established that SbWRKY75 directly regulates the expression of the flavonoid biosynthetic gene SbCLL-7, whereas SbWRKY41 directly regulates the expression of two other flavonoid biosynthetic genes, SbF6H and SbUGT, thus regulating baicalin biosynthesis. We also obtained transgenic S. baicalensis plants by somatic embryo induction and determined that overexpressing SbWRKY75 increased baicalin content by 41%, while RNA interference reduced it by 13%. Notably, SbWRKY41 indirectly regulated baicalin biosynthesis by modulating the expression of the transcription factor genes SbMYC2.1 and SbJAZ3. Moreover, SbWRKY41 can regulate SbWRKY75 expression, suggesting their joint involvement in the JA-mediated regulatory network underlying baicalin biosynthesis. These findings shed light on the molecular mechanism of JA-mediated baicalin biosynthesis.